B7H3-dependent myeloid-derived suppressor cell recruitment and activation in pulmonary fibrosis - Liu, Tianju; Gonzalez De Los Santos, Francina; Rinke, Andrew E.; Fang, Chuling; Flaherty, Kevin R.; Phan, Sem H. (Frontiers in Immunology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease without effective curative therapy. Recent evidence shows increased circulating myeloid-derived suppressor cells (MDSCs) in cancer, inflammation and fibrosis, with some of these cells expressing B7H3. We sought to investigate the role of MDSCs in IPF, and its potential mediation via B7H3. Here we prospectively collected peripheral blood samples from IPF patients to analyze for circulating MDSCs and B7H3 expression to assess their clinical significance and potential impact on co-cultured lung fibroblasts and T-cell activation. In parallel we assess MDSC recruitment and potential B7-H3 dependence in a mouse model of pulmonary fibrosis. Expansion of MDSCs in IPF patients correlated with disease severity. Co-culture of sB7H3-treated mouse M-MDSCs, but not G-MDSCs, activated lung fibroblasts and myofibroblast differentiation. Additionally sB7H3 significantly enhanced MDSC suppression of T cell proliferation. Activated M-MDSCs displayed elevated TGFβ and Arg1 expression relative to that in G-MDSCs. Treatment with anti-B7H3 antibodies inhibited bone marrow-derived MDSC recruitment into bleomycin-injured lung, accompanied by reduced expression of inflammation and fibrosis markers. Selective telomerase reverse transcriptase (TERT) deficiency in myeloid cells also diminished MDSC recruitment associated with reduced plasma level of sB7H3, lung recruitment of c-kit+ hematopoietic progenitors, myofibroblast differentiation and fibrosis. Lung scRNA-seq revealed fibroblasts as a predominant potential source of sB7-H3. Thus in addition to their immunosuppressive activity, TERT-dependent MDSC expansion/recruitment from BM could play a paracrine role to activate myofibroblast differentiation during pulmonary fibrosis with potential significance for disease progression mediated by sB7H3.